Anticancer effects of medical Malaysian leech saliva extract (LSE) - Merzouk, Ahmed; Mohammad Ghawi, Abbas; M.Abdualkader, Abdualrahman; Abdullahi, Abubakar Danjuma; Alaama, Mohammed (OMICS Publishing Group, 2012)
Leech saliva contains biologically active compounds that are mainly proteins & peptides. Small cell lung cancer (SCLC) is a form of cell lung carcinoma. In this study a modified and smooth extraction method of saliva was used without leech scarification. Trying to find out the biological activity of medical Malaysian Leech Saliva Extract as cytotoxic in vitro, the SW 1271 cell line was grown and maintained in Leibovitz’s L-15 medium supplemented with 10% foetal bovine serum at 37°C in normal atmospheric air. Serial dilutions of LSE were added to the cell line SW 1271 media for testing the cytotoxic activities.Result revealed that the LSE has a cytotoxic activity against small cell lung cancer(SW 1271 cell line) with IC50 of 119.844 μg/ml compared with IC50 values of two reference standard drugs Irinotecan (5.81 μg/ml) and Carboplatin(18.754 μg/ml). In a combination regimen, LSE reduced the IC50 of Carboplatin & Irinotecan by 65% & 11.5% respectively. Carboplatin reduced the IC50 of LSE by 4.6%, while Irinotecan reduced it by 57%. This results provides a promising novel agent for treatment of small cell lung cancer (SCLC) at least in vitro, more researches are needed